IN DEFENCE OF THEORETICAL ETHICS: A Critique on Amartya Sen’s The Idea of Justice - Chackalackal, Saju (Journal of Dharma, 2010)
Amartya Sen has made significant contributions to the understanding of the dynamics of poverty and its alleviation, global economics, and developmental paradigms. With the publication of The Idea of Justice (2009), the consequentialist agenda of Sen, an economist, has apparently become the most important word on justice. In tune with his rejection of ‘transcendental theories of justice’ offered by philosophers, Sen alleges that they are far removed from reality and are incapable of aiding the contemporary societies to overcome manifest injustice experienced. Hence, instead of following any idea of a perfect just society, Sen proposes that we must banish abstract theory and transcendentalism and should adopt a realizational model of justice to cure all ills of injustice. Sen’s position, perfectly in tune with the postmodern philosophical agenda where there cannot be any universal or ultimate anchor for human pursuits (as all anchors are fundamentally relative), assumes the garb of the theory of justice, although he rejects any theorizing as of any ultimate value.